2023
DOI: 10.1136/ard-2023-223885
|View full text |Cite
|
Sign up to set email alerts
|

Comparative safety and effectiveness of TNF inhibitors, IL6 inhibitors and methotrexate for the treatment of immune checkpoint inhibitor-associated arthritis

Abstract: ObjectivesTo compare the safety and effectiveness of biologic and conventional disease-modifying antirheumatic drugs (DMARDs) for immune checkpoint inhibitor-associated inflammatory arthritis (ICI-IA).MethodsThe retrospective multicentre observational study included patients with a diagnosis of ICI-IA treated with a tumour necrosis factor inhibitor (TNFi), interleukin-6 receptor inhibitor (IL6Ri) and/or methotrexate (MTX); patients with pre-existing autoimmune disease were excluded. The primary outcome was tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…12,13 However, besides the potential sideeffects, there is concern that at least some immunosuppressants could reduce the time to cancer recurrence. 14,15 This study highlights the potential role of PD-L1 + synovial macrophages and lends important preliminary support to further correlational studies in humans and mechanistic studies in mouse models to validate their findings. Although generalized depletion of myeloid cells by clodronate liposome treatment during disease induction in mouse models of autoimmune arthritis prevents arthritis, this approach also leads to the loss of subsets of macrophages that play an anti-inflammatory role.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…12,13 However, besides the potential sideeffects, there is concern that at least some immunosuppressants could reduce the time to cancer recurrence. 14,15 This study highlights the potential role of PD-L1 + synovial macrophages and lends important preliminary support to further correlational studies in humans and mechanistic studies in mouse models to validate their findings. Although generalized depletion of myeloid cells by clodronate liposome treatment during disease induction in mouse models of autoimmune arthritis prevents arthritis, this approach also leads to the loss of subsets of macrophages that play an anti-inflammatory role.…”
supporting
confidence: 54%
“…Disease‐modifying antirheumatic drugs such as methotrexate, tumor necrosis factor and interleukin 6R inhibitors can also be used 12,13 . However, besides the potential side‐effects, there is concern that at least some immunosuppressants could reduce the time to cancer recurrence 14,15 . This study highlights the potential role of PD‐L1 + synovial macrophages and lends important preliminary support to further correlational studies in humans and mechanistic studies in mouse models to validate their findings.…”
mentioning
confidence: 63%
“…In contrast, combination immunosuppressive treatment for irAE management (steroids with other medications) resulted in poor ICI treatment efficacy compared to prednisolone monotherapy in ipilimumab and nivolumab treatment for melanoma [ 12 ]. In addition, Bass et al have shown that TNF α inhibitor use for Rh-irAE treatment shortened the time to cancer progression compared to methotrexate [ 13 ]. Mitchell et al have also reported the possibility of decreased ICI efficacy by prolonged immunomodulation in patients receiving anti-programmed death-1 antibodies [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“… 107 In agreement with this there is evidence that treatment of irAE‐arthritis with biologic therapies, particularly anti‐TNF therapy, shortens the time to cancer progression, presumably preventing development of robust and persistent memory. 108 …”
Section: Persistence Of Rheumatic Iraesmentioning
confidence: 99%